Infection prevention and control, pillar for safety of healthcare worker: COVID-19 experience, Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Infection prevention and control (IPC) programs play an integral part in the safety of patients, visitors, health care workers and environment as these programs provide guidelines and standard for recognition, prevention and control of infection. With COVID-19 pandemic, Patan Hospital, Patan Academy of Health Sciences, Nepal, is amongst the few hospitals in Nepal to have undertaken the responsibility of managing COVID patients. The COVID response plan has been activated and is currently the best prepared institution to manage this pandemic.